PENGARUH KASIH SAYANG ORANG TUA TERHADAP KARAKTER RELIGIUS PESERTA DIDIK KELAS IV MIS AT-TAQWA SAMBAS - Yusfina Aprija (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2014)
This journal explains: 1) The love of parents for their children as class IV students of MIS At-Taqwa Sambas for the 2019-2020 Academic Year. 2) The religious character of the fourth grade students of MIS At-Taqwa Sambas for the 2019-2020 academic year. 3) There is the possibility of a significant effect of parental love on the religious character of the fourth grade students of MIS At-Taqwa Sambas for the 2019-2020 academic year. The type and research approach used is a quantitative research type and an associative approach. The population in this study amounted to 44 people. Data collection tools using questionnaires, documentation. The previous questionnaire was tried out and tested for validity and reliability testing. The data analysis technique used Percentage Calculation, Central Tendency and Simple Linear Regression. The results of this study can be concluded as follows: 1) Parents' affection for their children as fourth grade students of MIS At-Taqwa Sambas, is already classified as